GENERATION Z PARTICIPATION IN POLITICS AN APPROACH TO CONSUMER BEHAVIOR THEORY - Aries Kurniawan; Premananto, Gancar Candra; Candraningrat, Candraningrat; Aprilius, Adrianus; Hidayat, Rizky (Universitas Nahdlatul Ulama Surabaya, 2024)
Research aimed at finding out the causes of Generation Z playing an active role in politics was carried out using a qualitative methodology using phenomology. By using the snowball technique in determining informants, there were eight Generation Z students who were active in organizations or became organizational administrators. After going through triangulation, the researchers concluded that social media influences political attitudes, determining factors in political choices, political participation and perceptions of Generation Z in the political field. The conclusions obtained are in line with consumer behavior theory, especially the determining factors of political choices which are divided into two, namely rational and emotional factors.